Neurodevelopmental Outcomes After Assisted Reproductive Technologies - Balayla, Jacques (Obstet Gynecol, 2017)
OBJECTIVE: To compare children’s cognitive, motor, and language development at 2 years of age after assisted reproductive technologies (ARTs) relative to natural conception. METHODS: The 3D-Study (2010–2012) is a prospective cohort study, which sought to improve the understanding among perinatal events, obstetric outcomes, and child development. A total of 2,366 pregnant women were recruited, of whom 278 conceived with ART: ovarian stimulation, intrauterine sperm insemination, in vitro fertilization, intracytoplasmic sperm injection, or in vitro maturation. Natural conception was defined as the unassisted establishment of pregnancy. Cognitive, motor, and language neurodevelopmental outcomes were compared between ART and natural conception groups at 24 months using the Bayley Scales of Infant and Toddler Development, 3rd edition, and the MacArthur-Bates Communicative Development Inventories. Adjusted linear regression models evaluated the effect of ART on neurodevelopmental outcomes using natural conception as a reference. RESULTS: A total of 175 children in the ART group (62.9%) and 1,345 children in the natural conception group (64.4%) underwent neurodevelopmental assessment at 24 months postpartum. After adjusting for relevant confounders, children born after ART showed no difference in Bayley scales(’) cognitive scores (B(1) [standard error]=−1.60 [0.9], 95% confidence interval [CI] −3.36 to 0.16), composite motor scores (B(1) [standard error]=−1.33 [1.0], 95% CI −3.29 to 0.63), or MacArthur-Bates language scores (B(1) [standard error]=−0.28 [2.1], 95% CI −4.39 to 3.83). No difference was observed when independent ART techniques were compared nor when comparing in vivo (ovarian stimulation or intrauterine insemination) or in vitro (in vitro fertilization, intracytoplasmic sperm injection, or in vitro maturation) techniques (P>.05). CONCLUSION: Children born after ART had similar cognitive, motor, and language development as children born after natural conception at 2 years of age. These findings may be useful in the clinical counseling of patients undergoing ART.